The VvWRKY37 Regulates Bud Break in Grape Vine Through ABA-Mediated Signaling Pathways - Wang, Feng-Pan; Zhao, Pan-Pan; Zhang, Lei; Zhai, Heng; Abid, Muhammad; Du, Yuan-Peng (Frontiers in Plant Science, 2022)
Dormancy is a common survival strategy in plants to temporarily suspend visible growth under unsuitable conditions. The elaborate mechanism underlying bud break in perennial woody plants is gradually illustrated. Here, we identified a grapevine WRKY transcription factor, VvWRKY37, which was highly expressed in dormant buds. It was particularly induced by the application of exogenous abscisic acid, and depressed on exposure to gibberellin and low temperature (4 °C) stress at the transcript level. The yeast one-hybrid assay confirmed that VvWRKY37 had a transcriptional activity. Ectopic over-expression of VvWRKY37 significantly delayed bud break of transgenic poplar plants. As an ABA-inducible gene, VvWRKY37 also depressed the expression of ABA catabolic gene CYP707As and enhanced the accumulation of endogenous ABA in transgenic poplar plants. The molecular evidences showed that VvWRKY37 preferentially recognized and bound W-box 5′-G/CATTGACT/C/G-3′ cis-element in vitro. Additionally, VvABI5 and VvABF2 acted as the upstream transcriptional activators of VvWRKY37 via protein-DNA interactions. Taken together, our findings provided valuable insights into a new regulatory mechanism of WRKY TF by which it modulates bud break through ABA-mediated signaling pathways.